The Philosophy Behind My Forty-Five Years Successful Social Services (British Journal of Multidisciplinary and Advanced Studies, 2023)
During British rule, my grandfather the late Gopalsamy Gounder was an interesting attraction to the local office bearers and elected body members. He was one of the counselors for the Coimbatore Police Department by holding the  President of honorary office of Village Vigilance Committee My great grandfather the late Chinna Nachimuthu Gounder was a juror in the British ruling. Also, my father’s elder brother the late G. Shanmugasundaram[ commonly known as GS] served as the President of Kanjampatti Panchayat Board for 25 years namely from 1954 to 1979. During these four generations our family earned a good reputation in the society and accumulated a lot of experiences. Also, my mother’s father and her two eldest fathers served the poor and the needy. They were most popular and famous in Coimbatore district when the British ruled India. Two of them studied law in the 1920s and practiced in the Taluk and District courts. They helped the poor by attending their cases freely. My six uncles were highly cultured, qualified and interested in doing social services by helping the poor families. My mother’s father, the late Mylsamy Gounder, was the Village Munshif in the revenue department during the British rule of India. Their ancestors held this prestigious position for more than 100 years!These facts were told to me not by my family members but by my villagers and neighboring hamlets. Needless to say, our family was /is very familiar in more than 36 villages. These social services phenomena captivated my childhood and I made up my mind to become an EXTRAORDINARY & OUTSTANDING social worker.